2011
DOI: 10.1111/j.1467-7687.2010.01031.x
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of EEG power spectra in early adolescence: a longitudinal study

Abstract: This study investigated the fine-grained development of the EEG power spectra in early adolescence, and the extent to which it is reflected in changes in peak frequency. It also sought to determine whether sex differences in the EEG power spectra reflect differential patterns of maturation. A group of 56 adolescents were tested at age 10 years and then at two further time-points approximately 18 months apart. The EEG was recorded during both eyes-closed and eyes-open conditions and Fourier transformed to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
117
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(145 citation statements)
references
References 35 publications
26
117
0
2
Order By: Relevance
“…Interestingly, we observed no age differences in any of the frequency bands. This might due to the fact that our current frequency range (0-0.08 Hz) was significantly lower than what has been reported in the literature [e.g., 0.5-40 Hz in Cragg et al (2011); 2-13 Hz in Zhu et al (2011)]. Thus, differences in the frequency content of resting state neuronal oscillations is unlikely to have impacted our findings of age differences in network connectivity strength.…”
Section: Control Analysesmentioning
confidence: 57%
See 1 more Smart Citation
“…Interestingly, we observed no age differences in any of the frequency bands. This might due to the fact that our current frequency range (0-0.08 Hz) was significantly lower than what has been reported in the literature [e.g., 0.5-40 Hz in Cragg et al (2011); 2-13 Hz in Zhu et al (2011)]. Thus, differences in the frequency content of resting state neuronal oscillations is unlikely to have impacted our findings of age differences in network connectivity strength.…”
Section: Control Analysesmentioning
confidence: 57%
“…Thus, before comparing age groups in connectivity strength, we first evaluated the frequency content of the resting state BOLD signals among three age groups. Previous developmental studies have documented that there is a decreased power in the lower frequency band and an increased power in higher frequencies with age, throughout childhood and early adolescence (Cragg et al, 2011). By contrast, normal aging shows the opposite pattern; as a function of age, lower frequency power increases and higher frequency power decreases (Zhu et al, 2011).…”
Section: Control Analysesmentioning
confidence: 94%
“…1A). We deviated from the standard definition of frequency bands, since in developing young children the power spectrum is dominated by slow frequencies; the alpha peak occurs at slower frequencies (*8 Hz) in young children (Boersma et al, 2011;Marshall et al, 2002), which is in contrast with the faster alpha peak frequencies in adults (*10 Hz) (Cragg et al, 2011;Smit et al, 2011). To prevent splitting up the alpha band at this 8 Hz alpha peak and capturing as much slow oscillations as possible, we chose to combine the alpha and theta frequency bands, ranging from 4 to 10 Hz.…”
Section: Connectivity Matrix Formationmentioning
confidence: 99%
“…In the present study, in cases with trait EEG abnormality, the age of menarche was found to start at a younger age. In a more recent study, it was reported that in early puberty, EEG spectral power intensity changed developmentally and maturation occurred at different rates in both sexes (Cragg, Kovacevic, McIntosh, Poulsen, Martinu, Leonard, & Paus, 2011). According to the results of this prospective study, if compared in terms of EEG, female sex has a developmental delay interval.…”
Section: Discussionmentioning
confidence: 67%